Exposure doses to the population of Belarus from the Chernobyl accident in 2021–2025 - Mataras, Anastasia; Eventova, Ludmila; Batyan, Anatoly; Vlasova, Natalya; Visenberg, Yulia (Journal of the Belarusian State University. Ecology, 2023)
In accordance with the Laws of the Republic of Belarus «On the social protection of citizens affected by the accident at the Chernobyl NPP» dated January 6, 2009 and «On the legal regime of territories exposed to radioactive contamination due to the accident at the Chernobyl NPP» dated May 26, 2012, the value of the average annual effective dose of exposure to residents is one of the indicators of the radiation situation in settlements contaminated with radionuclides as a result of the Chernobyl accident. The objective: to update the method for assessing the exposure doses to the population in the situation of existing exposure after the Chernobyl accident and, on its basis, to assess the average annual effective exposure dose to residents of settlements of the Republic of Belarus due to the Chernobyl accident for the period 2021–2025. The method for estimating the average annual effective doses due to external and internal irradiation to residents of radioactively contaminated settlements of the Republic of Belarus has been improved taking into account international recommendations in the field of radiation protection, changes in the radiation situation in the long-time period after the Chernobyl accident and the new data on individual dosimetry of internal exposure to the population based on the results of whole-body counter (WBC) measurements. An assessment of the average annual effective exposure doses to the population of the Republic of Belarus residing in the territory of radioactive contamination was carried out, and based on its results, the Catalog of average annual effective exposure doses to residents of 2193 settlements for the period 2021–2025 was compiled. According to the compiled Catalog of average annual effective exposure doses to residents of settlements located on the territory of radioactive contamination of the Republic of Belarus, in 29 settlements out of 2193, the total effective exposure dose can exceed 1 mSv/year, in addition, it is about 1 mSv/year in 5 settlements. In none of the settlements, the average annual effective radiation dose can exceed 5 mSv/year. Valid for the period 2021–2025 Catalog of average annual effective exposure doses to the residents of settlements located on the territory of radioactive contamination of the Republic of Belarus, along with data on the density of contamination of the territories of the Republic of Belarus with long-lived radionuclides, was used to compile the List of settlements and objects located in the zones of radioactive contamination, and to adopt a Resolution of the Council of Ministers of the Republic Belarus on designation of settlements to the corresponding zones of radioactive contamination.
Keywords: internal exposure dose; external exposure dose; average annual effective exposure dose; settlement; representative person